Fine Mapping of a Novel defective glume 1 (dg1) Mutant, Which Affects Vegetative and Spikelet Development in Rice - Yu, Haiping; Ruan, Banpu; Wang, Zhongwei; Ren, Deyong; Zhang, Yu; Leng, Yujia; Zeng, Dali; Hu, Jiang; Zhang, Guangheng; Zhu, Li; Gao, Zhenyu; Chen, Guang; et al. (Frontiers in Plant Science, 2017)
In cereal crops, vegetative and spikelet development play important roles in grain yield and quality, but the genetic mechanisms that control vegetative and spikelet development remain poorly understood in rice. Here, we identified a new rice mutant, defective glume 1 (dg1) mutant from cultivar Zhonghua11 (ZH11) after ethyl methanesulfonate treatment. The dg1 mutant displayed the dwarfism with small, rolled leaves, which resulted from smaller cells and more bulliform cells. The dg1 mutant also had an enlarged leaf angle and defects in brassinosteroid (BR) signaling. In the dg1 mutant, both the rudimentary glume and sterile lemma (glumes) were transformed into lemma-like organ and acquired the lemma identity. Additionally, the dg1 mutant produced slender grains. Further analysis revealed that DG1 affects grain size by regulating cell proliferation and expansion. We fine mapped the dg1 locus to a 31-kb region that includes eight open reading frames. We examined the DNA sequence and expression of these loci, but we were not able to identify the DG1 gene. Therefore, more work will be needed for cloning and functional analysis of DG1, which would contribute to our understanding of the molecular mechanisms behind whole-plant development in rice.